5-function remote controller / Mohd Fitri Ishak and Mohd Ariff Mat Zohit - Ishak, Mohd Fitri; Mat Zohit, Mohd Ariff (2003)
The remote control car has long time ago invented, however the remote control car is not so popular among our society. It maybe because the cost of the car is too high and the product is not so attractive consider to the price. Nowadays the remote control (ar is like a trend in our community, the demand of the remote control car is increasing from time to time. This make the cost for purchasing the remote control car is decreasing, however we found that there are some problems with the remote control car that on the market today, we found that the remote control car produced by the manufacturer is actually in same frequency, so we have come up with an idea in building up the receiving and transmitting circuit which the frequency is different compared to the manufacturer’s standard. As we know that it is so important to have difference frequency so that there will be no collision in driving the remote control car. We will build the circuit that have five functions such as forwarding, backward, turning left, turning right and turbo powering the car. The standard toy car can be modified to increasing the speed of the toy car by adding some relay and changing the higher torque motor of the car.